Assembly of split aptamers by dynamic pH-responsive covalent ligation - Aho Aapo; Virta Pasi (ROYAL SOC CHEMISTRY, 2025)
Reversible pH-responsive N-methoxyoxazolidine formation is used to ligate split aptamer fragments. Two twice-split models and one thrice-split model of CBA (cocaine-binding aptamer) were examined. The aptamer assembly was dynamic, proportional to the substrate concentration and occurred without interfering background ligation.